The Effect of Gamma Irradiation 100 Gy on Stained Rice Seeds Msp-04 to on Vegetative and Generative Mutant Characters of M2 Generation - Ulfah, Silfiyah; Zainudin, Agus; Septia, Erfan Dani (Universitas Muhammadiyah Malang, 2024)
This study aims to obtain information on changes in the character of individual M2 generation mutant rice, similarities between individuals of the M2 generation mutant and its comparison, and correlation between variables. This research was conducted by observing the vegetative, generative, and potential yields of each individual rice mutant and its comparison. The data obtained were tested by cluster analysis and correlation analysis. The observations showed that almost all the characters of the M2 generation mutant individuals changed except for the qualitative vegetative characters. Cluster analysis based on quantitative vegetative character showed 1 different mutant individual (0% similarity), and 1 other individual with 38.83% similarity compared to other and non-mutant mutants, and commercial varieties. Based on quantitative and production generative characters, there are 2 distinct groups that differ from each other (0% similarity). The similarity range of each distinct group is 21.17-43.56%. The strong to very strong and very significant correlation that occurs in vegetative and generative characters with production is found between the number of tillers and panicles, total grain weight and dry grain weight of 98.7% each; 60.9% and 58.3%; the number of leaves is thus also between the number of panicles, total grain weight and dry grain weight respectively 91.3%; 53.3% and 53.4%; panicles with total grain weight and dry grain weight were 60.1% and 57.6%, respectively.